Coding of Non-coding RNA: Insights Into the Regulatory Functions of Pri-MicroRNA-Encoded Peptides in Plants - Ren, Yi; Song, Yue; Zhang, Lipeng; Guo, Dinghan; He, Juan; Wang, Lei; Song, Shiren; Xu, Wenping; Zhang, Caixi; Lers, Amnon; Ma, Chao; Wang, Shiping (Frontiers in Plant Science, 2021)
Peptides composed of short chain of amino acids can play significant roles in plant growth, development and stress responses. Numerous studies describe functions of secreted small peptides, which serve as local signal molecules mediating cell-to-cell communication and antimicrobial peptides (AMPs) responsible for plants' immune responses. Most of these functional peptides are derived by either processing of precursor proteins or direct translation of small open reading frames (ORFs) present in the genome and sometimes located in the untranslated regions (UTR) sequence of an mRNA. In recent years, increasing evidences from studies in both plants and animals have revealed that peptides are also encoded by RNAs currently defined as noncoding RNAs, including lncRNAs, circRNAs and pri-miRNAs. Pri-miRNAs, which are transcribed by RNA polymerase II (Pol II) and processed into microRNAs (miRNAs), have been reported to encode regulatory peptides in short ORFs localized in the upstream sequences of stem-loop structure. Such miRNA-encoded peptides (miPEPs) were identified in Arabidopsis, grapevine, soybean and medicago. Remarkably, overexpression or exogenous applications of miPEPs specifically increase the expression level of their corresponding miRNAs by enhancing the transcription of the MIRNA (MIR) genes. Here, we first outline the current knowledge regarding the biogenesis, biological functions and regulatory mechanisms of functional miPEP peptides in plants. Notably, we review in detail the limited studies available regarding translation of miPEPs and their relevant regulatory mechanisms. Furthermore, we discuss the potential cellular and molecular mechanisms in which miPEPs might be involved in plants and support problems that needed to be solved.